2009
DOI: 10.1007/s10484-009-9125-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Autogenic Training on General Improvement in Patients with Irritable Bowel Syndrome: A Randomized Controlled Trial

Abstract: Autogenic training (AT) is a useful and comprehensive relaxation technique. However, no studies have investigated the effects of AT on irritable bowel syndrome (IBS). In this study we tested the hypothesis that AT improves symptoms of IBS. Twenty-one patients with IBS were randomly assigned to AT (n = 11, 5 male, 6 female) or control therapy (n = 10, 5 male, 5 female). AT patients were trained intensively, while the control therapy consisted of discussions about patients' meal habits and life styles. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…A meta-analysis by Stetter and Kupper [23] also showed that AT was effective in addressing somatic symptoms. Moreover, several studies have reported that AT is effective in treating patients with specific diseases within the spectrum of FSS, such as IBS [24] and tension headache [26, 27]. The results of the present study do not contradict these findings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A meta-analysis by Stetter and Kupper [23] also showed that AT was effective in addressing somatic symptoms. Moreover, several studies have reported that AT is effective in treating patients with specific diseases within the spectrum of FSS, such as IBS [24] and tension headache [26, 27]. The results of the present study do not contradict these findings.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have investigated the influence of AT on different types of FSS, such as IBS [24], FMS [25], and tension headache [26, 27]. In these studies, AT elicited changes in physical and psychological measurements such as the patients’ physical symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Three trials provided effect sizes indicating greater improvement in the control group. 56,57,59 In 2 of these trials, the treatment group improved more than the control group on a dichotomous outcome measure identified by the authors as the primary outcome. 57,59 The remaining trial 56 used walking as a comparison condition, which could arguably be conceptualized as an active treatment rather than a control condition.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenic training is auto-hypnosis with the goal of being able to self-administer suggestions of relaxation. We reported that autogenic training is effective for intractable IBS patients [16]. Cognitive-behavioral therapy (CBT) focuses on ways to increase or decrease a particular behavior that addresses automatic thoughts and irrational beliefs.…”
mentioning
confidence: 99%